Relapse rate and outcome correlates in Egyptian patients with bipolar disorder treated with behavioural family psychoeducation. Issue 3 (July 2015) - Nagy, Nahla; Sabry, Walaa; Khalifa, Doaa; Hashem, Reem; Zahran, Nasser; Khalil, Afaf H.
Abstract : Background: Despite the extensive use of mood stabilizers, a high percentage of patients with bipolar affective disorder continue to experience frequent relapses. There is only a small and heterogeneous body of evidence on the effectiveness of behavioural family-oriented approaches for relapse prevention in patients with bipolar disorder. Aim: The aim of the study was to compare the relapse and hospitalization/rehospitalization rates in a group of patients with bipolar disorder who received behavioural family psychoeducation therapy and pharmacotherapy with the rates in a second group of bipolar patients who received supportive psychotherapy and pharmacotherapy. In addition, the study aimed to investigate the various sociodemographic correlates and clinical variables that affect the outcome of these patients. Patients and methods: Bipolar patients ( N =111) and their relatives were recruited immediately after an acute illness episode. They were randomly divided into two groups: group I and group II. Group I received 21 sessions of behavioural family therapy (BFT), and group II received a comparison treatment involving supportive psychotherapy sessions. Patients were simultaneously maintained on mood-stabilizing medications. We used the following parameters for assessment: Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I); Young Mania Rating Scale (YMRS), Hamilton Depression Rating Scale (HAM-D); Wisconsin Quality of Life Index Client Questionnaire (W-QLI); and the Social Functioning Questionnaire (SFQ). The main outcome measures included response rates, relapse rates and rate of rehospitalization. Results: Patients assigned to BFT had fewer relapses (25.3%) and hospitalizations/rehospitalizations (1.49%) during the study year compared with patients who received supportive psychotherapy (34.3 and 50%, respectively). None of the sociodemographic or clinical profile variables correlated with change in the outcome measures. Conclusion: BFT in combination with pharmacotherapy improves the outcome of bipolar illness by reducing relapse and hospitalization/rehospitalization rates. The study also demonstrated that BFT is effective for all patients across different sociodemographic and clinical backgrounds.